Implementasi Moderasi Beragama pada Budaya Organisasi Madrasah di MAN 3 Aceh Tenggara - Hamidah Hamidah; Najmuddin Najmuddin; Zahriyanti Zahriyanti (Journal on Education, 2025)
The aim of this research is to analyze national commitment, tolerance, non-violence and accommodating local culture in the organizational culture of MAN 3 Aceh Tenggara. This research uses a qualitative approach with a case study approach carried out at MAN 3 Aceh Tenggara. Data collection techniques are through observation, interviews and documentation. Data analysis techniques through triangulation, namely data reduction, data presentation and data verification. The research results show (1) national commitment is implemented through respecting diversity, mutual cooperation, concern for the nation and national pride, (2) tolerance is implemented through respecting differences in religious beliefs and practices, an open attitude towards inter-religious dialogue, avoiding religion-based discrimination, and building solidarity in diversity, (3) non-violence implemented by peaceful conflict resolution, respect for human rights (HAM), controlling emotions and assertive attitudes, and peace education, and (4) accommodating local culture implemented by respecting local traditions and customs , integration of religious and cultural values local, maintenance and preservation of positive traditions, tolerance for cultural diversity, and intercultural and religious dialogue.